Cronotopi slavi. Studi in onore di Marija Mitrović - Roic, Sanja; LAZAREVIC, Persida (Biblioteca di Studi Slavistici, 2013)
Cronotopi slavi is a collection of several essays written in honor of Marija Mitrovic by friends, colleagues and collaborators of the Universities of Trieste, Belgrade, Bloomington, Mainz, Turin, Chieti-Pescara, Udine, Zagreb, Fiume and Pola, who have shared and still share with her the passion for Slavistics and humanistic studies. The volume also includes the bibliography of the works of the eminent scholar of the University of Trieste.